2016
DOI: 10.1371/journal.ppat.1005547
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Is Activated during Congenital Cytomegalovirus Infection and Inhibits Neuronogenesis from Human Neural Stem Cells

Abstract: Congenital infection by human cytomegalovirus (HCMV) is a leading cause of permanent sequelae of the central nervous system, including sensorineural deafness, cerebral palsies or devastating neurodevelopmental abnormalities (0.1% of all births). To gain insight on the impact of HCMV on neuronal development, we used both neural stem cells from human embryonic stem cells (NSC) and brain sections from infected fetuses and investigated the outcomes of infection on Peroxisome Proliferator-Activated Receptor gamma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 51 publications
(78 reference statements)
7
70
2
Order By: Relevance
“…7 In our study, we explored the expression of the immediate early HCMV antigen (IE), a factor encoded by the HCMV genome and critical for virus replication, in histopathological slides from deceased infected or non-infected fetus. 8 In agreement with the studies in the mouse model, we observed cells clearly immunoreactive to IE in the ependymal and germinative zones of the brain of infected cases. However, no labeling was found in the white matter, whereas, as expected, brain vessels were positive to IE.…”
Section: Hcmv Tropism In the Developing Brainsupporting
confidence: 91%
See 4 more Smart Citations
“…7 In our study, we explored the expression of the immediate early HCMV antigen (IE), a factor encoded by the HCMV genome and critical for virus replication, in histopathological slides from deceased infected or non-infected fetus. 8 In agreement with the studies in the mouse model, we observed cells clearly immunoreactive to IE in the ependymal and germinative zones of the brain of infected cases. However, no labeling was found in the white matter, whereas, as expected, brain vessels were positive to IE.…”
Section: Hcmv Tropism In the Developing Brainsupporting
confidence: 91%
“…Last, we explored the relevance of these findings in vivo, through immunohistological examination of brain slices from a set of infected (N D 20) or uninfected control (N D 5) fetus of different gestational ages. Strinkingly, nuclear PPARg was immunodetected in the brain germinative zones of congenitally infected fetuses, but in none of the control samples 8 (Fig. 3), what strongly supported the role of PPARg in the disease phenotype.…”
Section: Role Of Pparg In Hcmv Neuropathymentioning
confidence: 59%
See 3 more Smart Citations